Two-year continuous measurements of carbonaceous aerosols in urban Beijing, China: Temporal variations, characteristics and source analyses. (June 2018) - Ji, Dongsheng; Yan, Yingchao; Wang, Zhanshan; He, Jun; Liu, Baoxian; Sun, Yang; Gao, Meng; Li, Yi; Cao, Wan; Cui, Yang; Hu, Bo; Xin, Jinyuan; et al.
Abstract: Organic carbon (OC) and elemental carbon (EC) in the PM2.5 of urban Beijing were measured hourly with a semi-continuous thermal-optical analyzer from Jan 1, 2013 to Dec 31, 2014. The annual average OC and EC concentrations in Beijing were 17.0 ± 12.4 and 3.4 ± 2.0 μg/m 3 for 2013, and 16.8 ± 14.5 and 3.5 ± 2.9 μg/m 3 for 2014. It is obvious that the annual average concentrations of OC and EC in 2014 were not less than those in 2013 while the annual average PM2.5 concentration (89.4 μg/m 3 ) in 2014 was slightly reduced as compared to that (96.9 μg/m 3 ) in 2013. Strong seasonality of the OC and EC concentrations were found with high values during the heating seasons and low values during the non-heating seasons. The diurnal cycles of OC and EC characterized by higher values at night and in the morning were caused by primary emissions, secondary transformation and stable meteorological condition. Due to increasing photochemical activity, the OC peaks were observed at approximately noon. No clear weekend effects were observed. Interestingly, in the early mornings on weekends in the autumn and winter, the OC and EC concentrations were close to or higher than those on weekdays. Our data also indicate that high OC and EC concentrations were closely associated with their potential source areas which were determined based on the potential source contribution function analysis. High potential source areas were identified and were mainly located in the south of Beijing and the plain of northern China. A much denser source region was recorded in the winter than in the other seasons, indicating that local and regional transport over regional scales are the most important. These results demonstrate that both regional transport from the southern regions and local accumulation could lead to the enhancements of OC and EC and likely contribute to the severe haze pollution in Beijing. Highlights: The average OC and EC concentrations did not decline as expected. The mass fractions of OC and EC in PM2.5 declined when the air quality deteriorated. No clear weekend effects were observed in contrast to developed regions. A much smaller source region was identified in the winter than in the other seasons.